Development of Project Based Science Learning Module to Improve Students’ Critical Thinking Skill - Yuliyanti Rahma Putri; Retno Triwoelandari; Yono Yono (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
Project based learning (PjBL) is a learning model which can encourage students to be more involved in their learning and to think critically. The purpose of this study is to produce project based science learning module for grade 5 Sekolah Dasar (SD)/Madrasah Ibtidaiyah (MI) as a product of this research. This research was a Research and Development (R&D) which was utilized the 4D model. The result showed that the module validation by material experts obtain a percentage of 75%, by linguists the percentage was 83.9%, and by media experts the percentage was 85, 5% so that the module made are declared feasible to be used in the classroom. Individual trials on 5 students the result was 88%. In the small group trial of 10 students the result was 92.8% and in the large group trial of 20 students the result was 96.7%. The results of initial observations and final observations showed an increase in students’ critical thinking skills with an average difference in individual trials of 21.80000, an average difference in small group trials of 21.40000 and average difference in large group trials of 21.55000. Apart from looking at the average differences in individual trials, small group trials, and large group trials, the average difference was also found in the experimental class which was treated with the control class which was not given treatment during the large group test, which was 10.60000. In conclusion, project based science learning module is effective in improving critical thinking skills of elementary students.